Disclosure of Information in the Company’s Annual Reports: A Bibliometric Analysis - Abdullah, Azrul; Waemustafa, Waeibrorheem; Mat Isa, Hamdan (2017)
This study evaluates the development of research publications towards the disclosure of information in companies’ annual reports.The aim is to provide a preliminary source of references for related scholars that interested in mapping research in this field.By using several bibliometric indicators, this study analyse all research publications related to disclosure of information in the company’s annual reports in the online Web of Science (ISI Thomson Reuters) database.This study examine the authorship, number of citations, journal sources, publishers, institutions, and countries, year of publication, categories, and author